2000
DOI: 10.1161/01.res.86.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Selective Upregulation of Cardiac Endothelin System in Patients With Ischemic but Not Idiopathic Dilated Cardiomyopathy

Abstract: Abstract-Only scarce information is available on the activity and modifications of the cardiac endothelin (ET)-1 system in heart failure due to ischemic (ICM) or idiopathic dilated (DCM) cardiomyopathy. The activity of the ET-1 system was investigated by measuring cardiac ET-1 and big ET-1 formation and quantifying cardiac mRNA for prepro-ET-1 (ppET-1), ET-converting enzyme-1, and ET A and ET B receptors both in myocardium and in isolated myocytes using Northern blot, reverse transcription-polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
3
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 59 publications
5
53
3
1
Order By: Relevance
“…It also has been shown that ET-1 mRNA receptor binding is increased in the hearts of diabetic rats [5,44], similar to what is found in cardiac disease [13]. In the present long-term study increased ET-1 and ETA receptor expression could also be demonstrated in diabetic rats.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It also has been shown that ET-1 mRNA receptor binding is increased in the hearts of diabetic rats [5,44], similar to what is found in cardiac disease [13]. In the present long-term study increased ET-1 and ETA receptor expression could also be demonstrated in diabetic rats.…”
Section: Discussionsupporting
confidence: 90%
“…One explanation proposed by some authors is that damaged cardiomyocytes are unable to synthesise ET-1 in response to Ang II stimulation [13,39,46]. For diabetes this explanation is excluded by our results.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…The A subtype receptor (ET A ) is mainly found in vascular smooth muscle cells as well as myocardium, myometrium and adrenal cortex. 8 8 ET A is encoded by the type A endothelin receptor (EDNRA) gene, which is a strong candidate gene for BP regulation. However, the few previously published candidate gene studies of EDNRA have in general been of small size, and most have typed only one polymorphism in the gene.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a previous study has demonstrated that the status of high big ET-1 level leads to a change of ET-1 receptor expression. 28 Therefore, as the reason for above discrepancy, there is one possibility that exogenous big ET-1 produces an altered ET-1 receptor expression. In the present study, however, the treatment with big ET-1 had no significant influence on the level of both ET A and ET B receptor mRNA expression in the left ventricle.…”
Section: Discussionmentioning
confidence: 99%